Marginalization and Power in Living with and Researching Living with HIV - Pedersen, Bodil (Outlines. Critical Practice Studies, 2005)
This article takes its point of departure in a research project studying the psychosocial problems of living with HIV. The project was intended to participate in changing practices dealing with these problems. It became a project including many differently situated and intersecting personal and generalized perspectives. The article researches the development of the HIV project as a contribution to discussions related to Participatory Action Research and Practice Research. In mainstream approaches methodological indications are often presented as rules to follow in order to ensure the quality of the obtained knowledge. But situated historical and societal processes are involved in the effectuation of the HIV project, like they are in any other project. Researching the project heightens the awareness of the necessity of reflecting on situated and historical issues of power and marginalization and on the positions of the researcher in a given field of research. Methodological flexibility may also be necessary in order to encompass different perspectives. Such reflections and strategies are necessary precisely to ensure the development of knowledge and practice alike.